Managerial economics : - Froeb, Luke M. (Thomsom South-Western, 2008)
This breakthrough text shows MBA's how to use economics to solve business problems. Succinct, faced paced, and challenging, students should be able to read the book from cover to cover and come away with a good understanding of how to diagnose business problems, and then fix them. With a lively, interactive approach, MANAGERIAL ECONOMICS focuses on the kinds of decisions managers face on a daily bases, making it an excellent resource for students pursuing business -- rather than academic -- careers.